CPC Futures The New Era of Socialism with Chinese Characteristics - Pieke, Frank N.; Hofman, Bert (NUS Press, 2022)
What will the upcoming 20th Congress of the Communist Party of China (CPC) bring, and what will the next decade of CPC rule look like? Who will rule China and what future do they envision for the Party and China? In this volume, the East Asian Institute in Singapore brings together an exceptional team of world-leading China experts from Asia, the United States, Europe and Australia to set out the future implications of trends in CPC politics and governance in CPC General Party Secretary Xi Jinping's "New Era." The essays collected in this volume bring together cutting-edge research and insights into the China's economy, society, politics, military and international relations targeted at for a professional audience in government, business, the media, NGOs and universities.